Error Correction Model: Factors Affecting Carbon Emissions in Supporting Sustainable Development in Indonesia - Fardin; Abd. Rahim; Citra Ayni Kamaruddin; Diah Retno Dwi Hastuti (Bulletin of Economic Studies (BEST), 2022)
This study is a study that aims to determine the effect of population, economic growth, and consumption of renewable energy on CO2 emissions in Indonesia. The type of data used in this study is secondary data and is time-series data from 1990-to 2019. The method of analysis in this study is the Error Correction Model (ECM) which aims to determine the existence of short-term and long-term relationships between the analyzed variables. Based on the results of data analysis conducted in this study, it can be concluded that in the short term population and consumption of renewable energy have no effect on CO2 emissions in Indonesia, while economic growth has a positive effect on CO2 emissions in Indonesia. In the long term, the results obtained are that population and economic growth have a positive effect on CO2 emissions in Indonesia, while consumption of renewable energy has no effect on CO2 emissions in Indonesia.